Tarekat dan Modal Sosial dalam Sistem Pendidikan Nahdlatul Wathan, 1966-1997 - Abdul Rasyad; Reiza D. Dienaputra; Mumuh Muhsin Zakaria; Raden Muhammad Mulyadi (Department of History, Faculty of Humanities, Diponegoro University, 2021)
Tarekat [Islamic congregation] is always interesting to be studied, including the Tarekat Hizib that developed in the Islamic organization of Nahdlatul Wathan (NW). This paper aims to explain the development and exposes a system of tarekat education and understand the social capital relations involved in the NW organization. This study is a historical study which is carried out in four stages, namely heuristics, criticism, interpretation, and historiography. According to the study, the education system developed by NW combines the salafiyyah [An education system that condemns theological innovation and advocates strict adherence to shari'a and to the social structures existing in the earliest days of Islam] and khalafiyyah, in which on the one hand maintains the traditional education in pesantren [Islamic boarding schools], but on the other hand also follows government regulations in implementing the national education system. Meanwhile, tarekat relations in the tarekat education system become a social capital in the religious life of NW followers and shaping the characteristics and personality of the community as well as the spiritual messages outlined by the tarekat founders. During the period 1966 to 1997, it was the main period as well as the antithesis in changing the orientation of the spiritual life perspective among the NW followers which has been getting stronger.